Exchange Rate Management: Intertemporal Tradeoffs - Helpman, Elhanan; Razin, Assaf (American Economic Review, 1987)
[Exchange rate management is possible only if the government pursues consistent monetary and fiscal policies. We construct a model in which the real consequences of exchange rate management depend on the precise time pattern of these policies. We study the constraints on feasible policies and the comparative dynamics of disinflation by means of exchange rate targetting. Our theoretical results are consistent wit exchange rate-managed disinflation attempts in Argentina, Chile, and Israel.]